Process mechanism in shape adaptive grinding (SAG). Issue 1 (2015) - Beaucamp, Anthony; Namba, Yoshiharu; Charlton, Phillip
Abstract Shape adaptive grinding (SAG) is a novel process for freeform machining of difficult materials such as ceramics and hard metals. Despite low stiffness requirement from the machining equipment, due to the "semi-elasticity" of the process (achieved by a combination of elastic tool with rigid pellets), ductile mode grinding can be achieved with high surface finish. In this paper, the SAG process mechanism is investigated by studying how the size and shape of the pellet bonded abrasives evolve over time, measuring grinding forces for various process parameters, and comparing the equivalent chip thickness and specific energy with the observed grinding modes.